Inclusive Education in Tripura: Perception of Special Educators and Children with Special Needs - Bhan, Sujata; Panshikar, Apoorva (JOURNAL OF INDIAN EDUCATION, 2024)
India is moving rapidly in the direction of providing inclusive education to all students, particularly Children with Special Needs. The special educators appear to be driving this effort by supporting the CwSN. In the present study, the respondents — the special educators and CwSN shared their experiences and perceptions about inclusive education in the State of Tripura. Data was collected using rating scales from both the sets of respondents and analysed. Results suggest that the special educators are working hard to reach out to all CwSN in the schools that they are employed, however, they feel ill-equipped to teach CwSN that they are not trained to teach. They seek collaboration from regular teachers. CwSN like their schools as they feel accepted by the peers and teachers, and indicate that they learn a lot in school.